2020
DOI: 10.21098/jimf.v6i2.1107
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media in Banks to Engender Women Empowerment and Financial Inclusion in Arab Countries

Abstract: This study aims to classify and interpret the interacted communications between banks and users on social media and understand the role of these digital platforms to enhance woman empowerments and financial inclusion in banks in Arab countries. 100 users of banks’ social media were selected from 5 leading banks in 5 Arab countries and their interactive utterances were classified, analyzed and interpreted. Content analysis tools were applied. The study reveals these key results: First, the use of social media i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…It has been found that financial inclusion leads to increased economic opportunities for low-income individuals, resulting in positive outcomes in social progress, economic development, and empowerment (Bhakar, 2017). Moreover, financial inclusion initiatives have been linked to supporting women's economic empowerment by enabling them to address challenges, provide better education for their children, access healthcare, and gain independence (Pal et al, 2021;Arshad, 2023;Yakubi et al, 2020).…”
Section: Relationship Between Financial Inclusion and Economic Empowe...mentioning
confidence: 99%
“…It has been found that financial inclusion leads to increased economic opportunities for low-income individuals, resulting in positive outcomes in social progress, economic development, and empowerment (Bhakar, 2017). Moreover, financial inclusion initiatives have been linked to supporting women's economic empowerment by enabling them to address challenges, provide better education for their children, access healthcare, and gain independence (Pal et al, 2021;Arshad, 2023;Yakubi et al, 2020).…”
Section: Relationship Between Financial Inclusion and Economic Empowe...mentioning
confidence: 99%
“…The first is the language barrier between the field researchers and the interviewees, not only in terms of using English instead of Arabic but also using a lexicon and jargon that researched communities do not understand. Moreover, in many cases, vulnerable groups, especially those living in remote areas, lack digital and financial literacy as well as access to finance, to the internet, and to digital tools (Yakubi, Basuki and Purwono 2019). This prevents researchers from fully reaching these groups, compensating them (in the case of remunerated interviews), and even formulating solutions for them to benefit from social protection programmes that require either digital literacy or financial literacy or both.…”
Section: Ids Bulletinmentioning
confidence: 99%